Enabling synergy through ta’aruf in strategic planning with Ulul albab approach for Masjid Tepi Sungai - Bilal Shah, Syed; Nik Abu Bakar, Nik Hajar Samihah; Kamarun-Niza, Hanis Solehah; Abdul Manan, Afifah Syahirah; Ahmad Sukri, Nurul Imanina; Ahmad Zaidi, Siti Sarah; Muhammad, Nurul Hanis; Zhang, Lu; Fayez, Mohammad Nasher; Mhd. Sarif, Suhaimi (2020)
This document reports the ta’aruf or ice-breaking session among consultants prior to conducting desktop research and proposal for strategic planning of Masjid Tepi Sungai (MTS). Ta’aruf or introduction enables members of consultants to bridge the gap of differences so that they could work in the consultancy without any barrier. In consultancy, every member plays significant role in making the consultancy rigorous, holistic and complete.